Endophytes for a Growing World 2019
DOI: 10.1017/9781108607667.003
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Novel Fungal Biological Control Agents for Plant Disease Control Among Endophytes

Abstract: There are increasing efforts aiming to utilise endophytes as biological control agents (BCAs) to improve crop production. However, reliability remains a major practical constraint for the development of novel BCAs. Many organisms are adapted to their specific habitat; it is optimistic to expect that a new organism added can find a niche or even out-compete those adapted and already present. Our approach for isolating novel BCAs for specific plant diseases is therefore to look in healthy plants in a habitat whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 118 publications
0
24
0
1
Order By: Relevance
“…On the basis of the accelerated depletion of the currently available fungicides, and the huge amounts of crops affected worldwide by plant pathogens, the upcoming generation of bioinoculants shall combine plant growth enhancement with biological control of plant pathogens (Collinge et al 2019). Notwithstanding that these bacterial strains harbor genes involved in biocontrol of plant diseases, bacteria inoculated individually were generally not able to control fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the accelerated depletion of the currently available fungicides, and the huge amounts of crops affected worldwide by plant pathogens, the upcoming generation of bioinoculants shall combine plant growth enhancement with biological control of plant pathogens (Collinge et al 2019). Notwithstanding that these bacterial strains harbor genes involved in biocontrol of plant diseases, bacteria inoculated individually were generally not able to control fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Since these microorganisms possess similar characteristics and share essentially the same biological niche as pathogens, it is relevant to understand their relationships and behaviour during disease outbreaks [16]. Moreover, some of these microorganisms may have the potential to be exploited in disease control as biological alternatives or to complement current control options [17]. If fungal endophytes were to be exploited as a new source of biocontrol agents, it would necessitate a thorough understanding of their behaviour when the pathogen arrives and the disease occurs [18].…”
Section: Introductionmentioning
confidence: 99%
“…secretion of antifungal compounds, mycophagy) have also been widely reported (Bonfante and Anca, 2009;Kobayashi and Crouch, 2009). Understanding and exploiting the association between different kinds of beneficial microorganisms, together with the management and engineering of the plant microbiome, may lead to improving soil fertility, crop productivity, and biological control of plant pathogens (Berg, 2009;Collinge et al, 2019;Compant et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have demonstrated in vitro that particular bacterial strains can be detrimental for the growth of S. indica (Varma et al, 2013) or in contrast have stimulatory effects, like strain WR5 of Azotobacter chrococcum, which enhanced mycelial growth and sporulation of S. indica in vitro (Bhuyan et al, 2015). In the last few years, some researchers have developed co-inoculations (microbial consortia) of fungi and bacteria, searching synergisms between two beneficial microbes (Artursson et al, 2006;Collinge et al, 2019). Special focus has been laid on the combination of S. indica with PGPR.…”
Section: Introductionmentioning
confidence: 99%